Some Specific Biological Risks of SARS-CoV-2 Infected Syrian Hamsters at Animal Biosafety Level - Lab 3 - Anna Vilkova; Islamov Rinat; Nurkeldi Turebekov; Gabdulrafik Sarsengaliyev; Alisher Salavatov; Galina Kovalyova (University of New South Wales, 2024)
The emergence of novel severe acute respiratory syndrome 2 (SARS-CoV-2) has prompted extensive research to identify its pathogenesis, transmission, and reservoir entry in animals. Syrian hamsters (Mesocricetus auratus) are being identified as an ideal animal model for the study of SARS-CoV-2 infection due to their susceptibility and respiratory symptoms similar to that observed in humans. This study focused on the specific biological risks associated with the use of infected Syrian hamsters in animal biosafety level 3 (ABSL-3) laboratories. The professional and psychological training of professionals working with laboratory animals should be a priority. Biological safety requires the involvement of all parties from technical staff to top management. The COVID-19 pandemic has shown a limitation in experimental studies when obtaining the right strain of mice proved difficult. A rare experimental model of Syrian hamsters started to be used in the work, which Syrian hamsters have several distinctive characteristics associated with increased aggressiveness of females, leading to a requirement to keep them isolated and some technical difficulties during manipulations in the biological safety cabinet. Therefore, a risk-based approach must be introduced to reduce the additional risks to workers to an acceptable level. This includes enhanced accuracy in the use of personal protective equipment (PPE), rigorously following biosecurity protocols, and monitoring staff health to detect potential risk of zoonotic transmission. The implementation of international standards and regulations on biological safety and biosecurity is of paramount importance.